2014
DOI: 10.2298/jas1403329o
|View full text |Cite
|
Sign up to set email alerts
|

Rural women farmers’ assessment of credit oriented self-help groups in Delta State, Nigeria

Abstract: This study was conducted to analyze the perception of the rural woman about credit oriented self-help group in Delta State, Nigeria. A sample size of 110 respondents was used for the study and data were collected from them with the use of structured interview schedule and questionnaires. Data were analyzed using descriptive statistics and linear regression equation model as the lead equation. It was revealed that the women farmers subscribed to self-help groups in order to be able to have access to credit (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Other expectations of members included training, catering for their needs, and provision of farm implements among others. The fact that the mean was low for the acquisition of agricultural information from farmers group contradicts the findings of Ofuoku and Albert (2014) who reported that one of the major reasons why women subscribe to groups was for information as it is very crucial to successful business transaction and farming activities. The least expectation of members for joining farmers group was to share ideas with each other and to pull resources together.…”
Section: Respondents' Expectations From Membership Of Farmer Groupsmentioning
confidence: 60%
“…Other expectations of members included training, catering for their needs, and provision of farm implements among others. The fact that the mean was low for the acquisition of agricultural information from farmers group contradicts the findings of Ofuoku and Albert (2014) who reported that one of the major reasons why women subscribe to groups was for information as it is very crucial to successful business transaction and farming activities. The least expectation of members for joining farmers group was to share ideas with each other and to pull resources together.…”
Section: Respondents' Expectations From Membership Of Farmer Groupsmentioning
confidence: 60%
“…This could be as a result of a high level of cooperative memberships among the farmers and the low interest rate charged by cooperative society compared with other informal sources of credit. Cooperative members harness their money through savings and use the accumulated savings to help members of the society financially with a little interest rate (Ofuoku and Albert, 2014). A similar result was reported by Edet et al.…”
Section: Resultsmentioning
confidence: 99%
“…Dissemination of information about knowledge of buffalo farming through social media groups could be done to increase farmers' access to information. The development and support of farmer groups who could independently manage and distribute information were needed to develop farmer groups in rural areas Ofuoku and Albert (2014). The participatory approach of livestock groups increased access to information based on information and communication technology (Barakabitze et al, 2017).…”
Section: The Correlation Between Farmers' Accessibility Of Resources ...mentioning
confidence: 99%